2017
DOI: 10.1016/j.medengphy.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trunnion roughness and length on the modular taper junction strength under typical intraoperative assembly forces

Abstract: Modular hip implants are at risk of fretting-induced postoperative complications most likely initiated by micromotion between adjacent implant components. A stable fixation between ball head and stem-neck taper is critical to avoid excessive interface motions. Therefore, the aim of this study was to identify the effect of trunnion roughness and length on the modular taper strength under typical intraoperative assembly forces. Custom-made Titanium trunnions (standard/mini taper, smooth/grooved surface finish) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 63 publications
3
16
0
Order By: Relevance
“…When the relation of the pull-off force to the dynamic load of 3 kN was compared, it was nearly the same as in the static group, with a mean relation of 53% (intact: 50%, scratched: 59%, and truncated: 50%). This is in line with previous studies, which showed a linear relationship between assembly and pull-off force [4,18,31,37]. In further investigations, an assembly load above the maximum load during dynamic testing has to be analysed in order to determine whether the dynamic load has an influence on the fixation strength of the taper connection.…”
Section: Discussionsupporting
confidence: 78%
“…When the relation of the pull-off force to the dynamic load of 3 kN was compared, it was nearly the same as in the static group, with a mean relation of 53% (intact: 50%, scratched: 59%, and truncated: 50%). This is in line with previous studies, which showed a linear relationship between assembly and pull-off force [4,18,31,37]. In further investigations, an assembly load above the maximum load during dynamic testing has to be analysed in order to determine whether the dynamic load has an influence on the fixation strength of the taper connection.…”
Section: Discussionsupporting
confidence: 78%
“…When all other parameters are equal, MacLeod's model estimates a higher fixation force than Fessler's model by about a third ( Figure 2). However, when considering the technical aspects of the different experimental setups, nearly all fixation force values described in the literature correspond to the values estimated by Fessler's formula, ranging 40% to 55% of the impaction force [6,21,44,[47][48][49][50][51][52]. Surprisingly, the values measured by MacLeod et al do not correspond to those estimated by their own model [43].…”
Section: Technical Aspects Of Taper Connections In Hip Arthroplastymentioning
confidence: 70%
“…In both models, the fixation force correlates linearly with the force applied to impact the taper. The fixation force, therefore, has a major effect on the stability of the taper connection [6,[44][45][46][47][48][49][50][51][52]. Because the taper angle α is determined by the chosen prosthesis design (typically between 5 • 30 and 6 • [36]), this parameter has to be considered as fixed.…”
Section: Technical Aspects Of Taper Connections In Hip Arthroplastymentioning
confidence: 99%
See 1 more Smart Citation
“…Machined profiles on trunnions used with ceramic heads were introduced to reduce tensile stresses at the taper interface, but trunnions with threaded stems are now commonly mated with either ceramic or metal head tapers . In addition surgical factors such as low impaction force (<4 kN), off‐axis impaction and taper contamination coupled with an increase in trunnion flexibility, due to the use of lower elastic modulus alloys, have all been reported to facilitate crevice corrosion . Taper geometry itself has evolved, including a reduction in both taper diameter and trunnion length .…”
Section: Introductionmentioning
confidence: 99%